Knowledge regarding cervical, cancer and its screening among women at Mankweng Hospital, Limpopo Province, South Africa - Phaahla, Paulina Manchadi (My University, 2017)
Refer to document
Thesis (MPH.) -- University of Limpopo, 2017
Keywords: Cervical cancer; Cervical cancer screening; Knowledge; Cervix Uteri -- Screening